Structure and organization of coffee value chains in Ethiopia - Hiwot Abayneh Ayele; Anne Margarian; Daniela Weible (Johann Heinrich von Thünen-Institut, 2026)
Motivation The high level of regulation has a strong influence on the development of Ethiopia's export- and domestic- oriented coffee value chains, as well as on their ability to participate in Global Value Chains and in domestic value chain development. The fact that Ethiopia's coffee value chains are further differentiated along various dimensions is widely overlooked in the scientific literature. Approach and methods Drawing on expert interviews and other data sources, we identify, describe, and discuss the structure and organisation of the Ethiopian coffee value chains, taking into account institutional conditions and policy frameworks. We also identify relevant institutions and policies involved in these value chains across primary, secondary, and tertiary markets, along with their respective interventions. Findings Our analysis identified four major coffee value chains: formal, informal, domestic, and international chains. Stakeholders' competing goals and conflicts have created a complex structure, as exemplified by the strict market regulations in place. Reforms, such as Ethiopia's monetary policy, have caused foreign exchange and FDI deficits, impacting the coffee sector, which remains the primary source of foreign currency but limits domestic coffee development. This also spurred informal trade for local and cross-border markets. An overvalued currency and cheap imports attract informal traders, as exporters seek foreign currency through coffee, thereby hindering the sector's development. Poor quality control further restricts the competitiveness of domestic chains, favouring small, inefficient, and informal traders. Institutions failed to regulate reforms, such as the 2018 coffee reform, which reduced transparency and undermined trust. Furthermore, the failure of institutions to monitor and regulate policy reform meant that farmers, primary cooperatives, and traders working on quality considered it a less rewarding activity. The Ethiopian coffee market does not function effectively in terms of differentiating and remunerating different product and process qualities. Policy implications The results highlight the need to implement quality control measures at farm level, particularly within the farmer-supplier-exporter chain, in order to utilize the country's potential to produce high-quality coffee for export and develop the domestic value chain. This also calls for designing a system that rewards quality production at all stages of the value chain. Acknowledging the distinct coffee value chains in the country and creating a strategy that considers their variations is crucial.
urn:nbn:de: gbv:253-2026-000031-3
Keywords: 630; Coffee; value chain analysis; coffee market; institutional environment; Ethiopia